Time tracing the earliest case of local pandemic resurgence - Zhang, Jianing; Fang, Kexin; Zhu, Yinhua; Kang, Xiaoyun; Zhang, Lin (Frontiers in Physics, 2023)
Origin identification of the earliest cases during the pandemic is crucial in containing the spread of the disease. The high infectiousness of the disease during its incubation period (no symptom yet) and underlying human interaction pattern make it difficult to capture the entire line of the spread. The hidden spreading period is when the disease is silently spreading, for the ‘silent spreaders’ showing no symptoms yet are able to transmit the infection. Uncertain of the hidden spreading period would bring a severe challenge to the contact tracing mission. To find the possible hidden spreading period span, we utilized the SEITR (susceptible - exposed- infected - tested positive - recovered) model on networks where the relation between E state and T state can implicitly model the hidden spreading mechanism. We calibrated the model with real local resurgence epidemic data. Through our study, we found that the hidden spreading period span of the possible earliest case of local resurgence could vary according to the people interaction networks. Our modeling results showed the clustering and shortcuts that exist in human interaction network affects the results in finding the hidden spreading period span greatly. Our study can be a guide for understanding the pandemic and contact tracing the origin of local resurgence.